A eficiência dos serviços de água e esgoto do estado do Ceará - Cardoso, Pedro Herlleyson Gonçalves (2023)
This thesis analyzed the water and sewage services in Ceará, based on three essays. The first essay analyzed, from the database of the National Sanitation Information System (SNIS), the technical efficiency of water and sewage services in municipalities in the state of Ceará, as well as the change in the total productivity of the factors used in the provision of these services in the period from 2005 to 2017. For this purpose, Data Envelopment Analysis (DEA) was used to build an efficiency frontier for the water and sewage service and the Malmquist Index to measure changes in the total productivity of these services. factors of these services. The results showed that while the number of municipalities operating on the efficiency frontier increased only slightly, the mean efficiency scores decreased significantly. It was also found that the total factor productivity decreased over the period of analysis, whose change was determined by the decrease in the degree of technical efficiency and retrogression in technology. The second essay analyzed, from the SNIS database, the determining factors of operational performance, and its distributive effects of water and sewage services in municipalities in the state of Ceará, in the period from 2005 to 2020. factor analysis was used to determine the factors to measure the Operating Performance Index (OPI). Subsequently, quantile regression was performed to identify distributive effects. The results show that the average tariff practiced, the Index of losses in distribution, and the Index of water consumption were the variables that best explained the progress in the performance of water and sewage services in the analyzed municipalities. On the other hand, the total number of own employees and the Urban Sewage Service Index referred to the municipalities served with sewage were the variables that least explained the progress in performance. The third essay analyzed, from the SNIS database, the System of the Federation of Industries of the State of Rio de Janeiro (FIRJAN) and the Brazilian Institute of Geography and Statistics (IBGE), the effect of the socioeconomic characteristics of the administrative mesoregions of the state of Ceará on the operational performance of water and sewage services in municipalities in the state of Ceará, grouping them into clusters. For this purpose, quantile regression analysis and cluster analysis were used. The results showed that indicators such as the Human Development Index (HDI) and health have a negative effect on the performance of water and sewage services, especially in municipalities with the highest operational performance, with the North/Northwest and Metropolitana of Fortaleza administrative mesoregions showing better results. Municipalities with intermediate operational performance tend to have a positive effect on the Gini Index and on education. Furthermore, the study also showed that the national basic sanitation policy has a positive effect on the performance of water and sewage services, especially in municipalities with lower operational performance.